Dental hygienists' knowledge of HIV, attitudes towards people with HIV and willingness to conduct rapid HIV testing. Issue 4 (10th April 2013) - Santella, AJ; Krishnamachari, B; Davide, SH; Cortell, M; Furnari, W; Watts, B; Haden, SC
Abstract Objectives To normalize rapid human immunodeficiency virus (HIV) testing in the United States, expanded rapid HIV testing initiatives are needed outside the routine medical setting. The dental setting is a logical choice as almost two‐thirds of Americans regularly see a dental provider each year. This study was aimed to determine the dental hygienists' knowledge of HIV, attitudes towards people living with HIV and willingness to conduct rapid HIV testing. Methods A national cross‐sectional survey of practicing dental hygienists and senior dental hygiene students were recruited using state dental hygiene associations, email LISTSERVS, dental hygiene programmes and continuing education conferences (n = 634). Results The mean knowledge score was 10.5/13. High versus low test‐scorers (75% of test questions or more answered correctly versus less than 75% answered correctly) did differ in their comfort level in counselling about sexual HIV prevention methods (P = 0.03) and comfort level in working with medically compromised patients (P = 0.04). Conclusion Dental hygienists, with additional training in HIV prevention counseling and diagnostic testing, may be an appropriate profession to conduct rapid HIV testing.